Is there a difference in labor patterns after induction with prostaglandins and double-balloon catheters?AJOG Global Reports at a Glance - Hila Shalev-Ram, MD; Roi Cirkin, MD; Gal Cohen, MD; Shai Ram, MD; Yoram Louzoun, MD; Michal Kovo, MD; Tal Biron-Shental, MD (Elsevier, 2023)
BACKGROUND: Labor progression curves are believed to differ between spontaneous and induced labors. However, data describing labor progression patterns with different modes of induction are insufficient. OBJECTIVE: This study aimed to compare the progress patterns between labors induced with slow-release prostaglandin E2 vaginal analogue and those induced with a double-balloon catheter. STUDY DESIGN: This retrospective cohort study included all nulliparous women who delivered at term and who underwent cervical ripening with prostaglandin E2 vaginal analogue or a double-balloon catheter from 2013 to 2021 in a tertiary hospital in Israel. Included in the analysis were women who achieved 10 cm cervical dilatation. The time intervals between centimeter-to-centimeter changes were evaluated. RESULTS: A total of 1087 women were included of whom 786 (72.3%) were induced using prostaglandin E2 vaginal analogue and 301 (27.7%) were induced using a double-balloon catheter. The time from induction to birth was similar between the groups (32.5 hours for the prostaglandin E2 vaginal analogue group [5th-95th percentiles, 6.5-153.8] vs 29.2 hours for the double-balloon group [5th-95th percentiles, 9.1-157.1]; P=.100). The median time of the latent phase (2-6 cm dilation) was longer for the double-balloon catheter group than for the prostaglandin E2 vaginal analogue group (7.3 hours [5th-95th percentiles, 5.6-14.5] vs 6.0 hours [5th-95th percentiles, 2.4-18.8]; P=.042). The median time of active labor (6-10 cm dilatation) was similar between groups (1.9 hours [5th-95th percentiles, 0.3-7.4] for the prostaglandin E2 vaginal analogue group vs 2.3 hours [5th-95th percentiles, 0.3-6.5] for the double-balloon catheter group; P=.307). CONCLUSION: Deliveries subjected to cervical ripening with a double-balloon catheter were characterized by a slightly longer latent phase than deliveries induced by prostaglandin E2 vaginal analogue. After reaching the active phase of labor, the mode of cervical ripening did not influence the labor progress pattern.